The heterogeneous mechanical properties of adolescent growth plate cartilage: A study in rabbit. (April 2022) - Eckstein, Kevin N.; Thomas, Stacey M.; Scott, Adrienne K.; Neu, Corey P.; Hadley-Miller, Nancy A.; Payne, Karin A.; Ferguson, Virginia L.
Abstract: The growth plate is a cartilaginous tissue that functions to lengthen bones in children. When fractured, however, the growth plate can lose this critical function. Our understanding of growth plate fracture and mechanobiology is currently hindered by sparse information on the growth plate's microscale spatial gradients in mechanical properties. In this study, we performed microindentation across the proximal tibia growth plate of 9-week-old New Zealand White rabbits (n = 15) to characterize spatial variations in mechanical properties using linear elastic and nonlinear poroelastic material models. Mean indentation results for Hertz reduced modulus ranged from 380 to 690 kPa, with a peak in the upper hypertrophic zone and significant differences (p < 0.05) between neighboring zones. Using a subset of these animals (n = 7), we characterized zonal structure and extracellular matrix content of the growth plate through confocal fluorescent microscopy and Raman spectroscopy mapping. Comparison between mechanical properties and matrix content across the growth plate showed that proteoglycan content correlated with compressive modulus. This study is the first to measure poroelastic mechanical properties from microindentation across growth plate cartilage and to discern differing mechanical properties between the upper and lower hypertrophic zones. This latter finding may explain the location of typical growth plate fractures. The spatial variation in our reported mechanical properties emphasize the heterogeneous structure of the growth plate which is important to inform future regenerative implant design and mechanobiological models. Graphical abstract: Image 1 Highlights: Mechanical properties differ between the proliferative, upper hypertrophic, and lower hypertrophic zones of the growth plate. These results may help explain the location of typical growth plate fractures. Compressive modulus correlated with relative proteoglycan content.